Stabilization of angiotensin-(1-7) by key substitution with a cyclic non-natural amino acid - Wester, Anita; Devocelle, Marc; Tallant, E. Ann; Chappell, Mark C.; Gallagher, Patricia E.; Paradisi, Francesca (Springer, 2017)
Angiotensin-(1-7) [Ang-(1-7)], a heptapeptide hormone of the renin-angiotensin-aldosterone system (RAAS), is a promising candidate as a treatment for cancer that reflects its antiproliferative and anti-angiogenic properties. However, the peptide’s therapeutic potential is limited by the short half-life and low bioavailability resulting from rapid enzymatic metabolism by peptidases including angiotensin-converting enzyme (ACE) and dipeptidyl peptidase 3 (DPP 3). We report the facile assembly of three novel Ang-(1-7) analogues by solid-phase peptide synthesis which incorporates the cyclic non-natural δ-amino acid ACCA. The analogues containing the ACCA substitution at the site of ACE cleavage exhibit complete resistance to human ACE, while substitution at the DDP3 cleavage site provided stability against DPP 3 hydrolysis. Furthermore, the analogues retain the anti-proliferative properties of Ang-(1-7) against the 4T1 and HT-1080 cancer cell lines. These results suggest that ACCA-substituted Ang-(1-7) analogues which show resistance against proteolytic degradation by peptidases known to hydrolyze the native heptapeptide may be novel therapeutics in the treatment of cancer.